Survey and first molecular characterization of Banana bunchy top virus infecting Musa spp. cv. Sabri in Bangladesh - Md. Anowar, Hossain; MD. AHSAN, HABIB; MD. FARHAD, ALAM; MOHD TANVIR, HAIDER CHOWDHURY; KHADIZA, ISLAM; Hairul Azman, Roslan; Md. Rezaul, Karim (Taylor & Francis Group, 2025)
Banana bunchy top virus (BBTV) is a major viral pathogen in bananas, capable of causing up to 100% yield loss. This study investigated the prevalence and molecular characterization of BBTV in three major banana-growing districts – Rajshahi, Natore and Pabna – in Bangladesh. Field surveys revealed that BBTV was the most widespread viral disease, with a 62.7% infection rate in Musa sp. cv. Sabri. All six genomic components (DNA-R, -U3, -S, -M, -C, and -N) of BBTV were successfully amplified using gene-specific primers from isolates in all three districts. DNA sequencing of the Rajshahi isolates revealed 99.96–100% nucleotide identity with the corresponding genomic components of isolates from Natore and Pabna. BLASTn analysis revealed 92–98% nucleotide identity with known BBTV sequences, indicating a close relationship with Indian isolates. Phylogenetic analysis suggests that the Rajshahi isolates belong to the South Pacific group. The six primer sets used in this study proved effective for BBTV detection and are suitable for indexing virus-free tissue culture banana seedlings. This is the first molecular confirmation of BBTV infection in the Sabri cultivar in Bangladesh, underscoring a significant threat to regional banana production and the need for urgent management strategies.